2012
DOI: 10.1007/s10459-012-9430-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effectiveness of a game informed online learning activity and face to face teaching in increasing knowledge about managing aggression in health settings

Abstract: Citation: McKenzie, Karen (2013) A comparison of the effectiveness of a game informed online learning activity and face to face teaching in increasing knowledge about managing aggression in health settings. Advances in Health Sciences Education, 18 (5 Northumbria University has developed Northumbria Research Link (NRL) to enable users to access the University's research output. Copyright © and moral rights for items on NRL are retained by the individual author(s) and/or other copyright owners. Single copies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
2
6
0
1
Order By: Relevance
“…Furthermore, there was a low willingness to participate in the e-learning programme, possibly due to the requirement to separately register for this programme. However, studies also show that students and participants of health interventions prefer face-to-face training 11 12. Similar to other behavioural studies, factors such as self-report, social desirability and recall bias may have influenced our findings, as well as lack of blinding which was not feasible in this study 20 23.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Furthermore, there was a low willingness to participate in the e-learning programme, possibly due to the requirement to separately register for this programme. However, studies also show that students and participants of health interventions prefer face-to-face training 11 12. Similar to other behavioural studies, factors such as self-report, social desirability and recall bias may have influenced our findings, as well as lack of blinding which was not feasible in this study 20 23.…”
Section: Discussionsupporting
confidence: 54%
“…Studies have shown that knowledge—regardless of the topic—can be increased through both face-to-face and online training. However, face-to-face training is rated much more positively than pure online learning 11–13. Mobile health (mHealth) is one promising approach in cancer prevention, with text message (short message service, SMS)-based programmes being used worldwide 14…”
Section: Introductionmentioning
confidence: 99%
“…Both groups were similar in problem selection, length of unit, number of materials, organisation of student groups and integration of technology. McKenzie (2013) found that medical students in F2F classes gave significantly higher ratings to teaching staff and reported greater knowledge attainment, which was supported by higher test scores. The researchers suggested these differences may have been due to both technical limitations with the online version of the course (which constrained the complexity of online activity) and the greater complexity and feedback opportunities that were permitted within the F2F course.…”
Section: Resultsmentioning
confidence: 70%
“…By learning through SGs, for instance, students have increased their knowledge as well as self‐efficacy for healthy eating habits (Peng, 2009). Similarly, McKenzie (2013) suggested that students trained via SGs increased their self‐efficacy in dealing with aggressive situations.…”
Section: Introductionmentioning
confidence: 99%